2011
DOI: 10.1186/1471-2164-12-s3-s3
|View full text |Cite
|
Sign up to set email alerts
|

Liverome: a curated database of liver cancer-related gene signatures with self-contained context information

Abstract: BackgroundHepatocellular carcinoma (HCC) is the fifth most common cancer worldwide. A number of molecular profiling studies have investigated the changes in gene and protein expression that are associated with various clinicopathological characteristics of HCC and generated a wealth of scattered information, usually in the form of gene signature tables. A database of the published HCC gene signatures would be useful to liver cancer researchers seeking to retrieve existing differential expression information on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(45 citation statements)
references
References 23 publications
2
43
0
Order By: Relevance
“…The data suggest reprogramming of one-carbon metabolism in HCC. This is consistent with the Liverome study reporting that downregulation of MTHFD1 is prevalent in proliferative and poorly differentiated HCCs 38 .…”
Section: Proteins With Altered Abundance In Hcc Patients With High Sesupporting
confidence: 93%
“…The data suggest reprogramming of one-carbon metabolism in HCC. This is consistent with the Liverome study reporting that downregulation of MTHFD1 is prevalent in proliferative and poorly differentiated HCCs 38 .…”
Section: Proteins With Altered Abundance In Hcc Patients With High Sesupporting
confidence: 93%
“…Among target genes, 130 genes have been associated with HCC in at least one previous report by comparing with Liverome database (http://liverome.kobic.re.kr/). [21] Upon further evaluation for enriched biological function, we identified several important biologic pathways, including transforming growth factor beta (TGFβ) receptor signaling pathway, endocytosis, signaling by epidermal growth factor receptor, signaling by nerve growth factor (NGF), NGF signaling via tropomyosin receptor kinase A from the plasma membrane, BMAL1: CLOCK/NPAS2 activates circadian expression and adherens junction [Supplementary Table 7], which confirmed the potential biological role of HCC specific miRNAs involved in tumorigenesis.…”
Section: Resultsmentioning
confidence: 99%
“…HCCs are highly heterogeneous, and it is unlikely that a single marker will be found that is expressed in 100% of patients . Di Tommaso et al .…”
Section: Gpc3 As a Marker For Hccmentioning
confidence: 99%
“…HCCs are highly heterogeneous, and it is unlikely that a single marker will be found that is expressed in 100% of patients [30]. Di Tommaso et al have shown that the simultaneous use of GPC3, heat shock protein 70 (HSP70) and glutamine synthetase (GS) immunostaining could significantly increase sensitivity without reducing specificity of the GPC3-only based diagnosis of HCC [31,32].…”
Section: Gpc3 As a Marker For Hccmentioning
confidence: 99%